Dynamics of an Anisotropic Universe in f(R,T) Theory - B. Mishra; Sankarsan Tarai; S. K. Tripathy (Advances in High Energy Physics)
Dynamics of an anisotropic universe is studied in f(R,T) gravity using a rescaled functional f(R,T), where R is the Ricci Scalar and T is the trace of energy-momentum tensor. Three models have been constructed assuming a power law expansion of the universe. Physical features of the models are discussed. The model parameters are constrained from a dimensional analysis. It is found from the work that the anisotropic Bianchi type VIh (BVIh) model in the modified gravity generally favours a quintessence phase when the parameter h is either -1 or 0. We may not get viable models in conformity with the present day observation for h=1.